2007
DOI: 10.1002/cjoc.200790227
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Adsorption and Self Assembly of Isocyanide Derivatives on Au(111) Surface

Abstract: The adsorption and self-assembly of isocyanide derivatives on Au(111) surface were investigated by density functional theory (DFT) and molecular dynamics simulation. The calculation for phenyl isocyanide by DFT was based on cluster and slab models. The self-assembled monolayers of 2-isocyanoazulene and 1,3-diethoxycarbonyl-2-isocyanoazulene on Au(111) were simulated using Au-C force field parameters developed by us. It was found that the top site was the most preferred position, and the isocyanoazulene and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…In addition, the presence of a single CN vibrational mode is consistent with the proposed structure, since the isocyanide groups are symmetrically equivalent and will therefore only give rise to a single, infrared-allowed vibrational mode. The isocyanide stretching frequency is shifted from the gas-phase value of 2123 cm -1 , consistent with the formation of an isocyanide bond with the surface [22][23][24][25][26][39][40][41][42][43][44][45][46][47][48][49]. Both the C-H bending and CN stretching modes shift somewhat with coverage, and this effect is likely to be due to vibrational coupling between modes in adjacent one-dimensional chains as the coverage increases, and they come closer together.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In addition, the presence of a single CN vibrational mode is consistent with the proposed structure, since the isocyanide groups are symmetrically equivalent and will therefore only give rise to a single, infrared-allowed vibrational mode. The isocyanide stretching frequency is shifted from the gas-phase value of 2123 cm -1 , consistent with the formation of an isocyanide bond with the surface [22][23][24][25][26][39][40][41][42][43][44][45][46][47][48][49]. Both the C-H bending and CN stretching modes shift somewhat with coverage, and this effect is likely to be due to vibrational coupling between modes in adjacent one-dimensional chains as the coverage increases, and they come closer together.…”
Section: Discussionsupporting
confidence: 65%
“…This shows peaks at 2137 and 813 cm -1 at a saturation PDI coverage. These modes can be assigned quite straightforwardly to the CN stretching mode (at *2137 cm -1 ) [22][23][24][25][26][39][40][41][42][43][44][45][46][47][48][49], and an out-of-plane C-H bending mode for the benzene ring (813 cm -1 ), which is the only detectable mode in the CH fingerprint region. The out-of-plane bending mode, according to the surface infrared selection rules [21], should be allowed for a benzene ring lying parallel to the surface.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular orientations of isocyanides adsorbed on metal surface were investigated both theoretically [52][53][54][55][56] and experimentally. 30,57,58 However, the preferred molecular orientations of isocyanides still remain unresolved.…”
Section: Resultsmentioning
confidence: 99%
“…Zhou et al showed that MPI is standing straight on a terminal site of Au. 55 According to the recent DFT calculations of PDI on an Au(111) surface, the energy difference between the geometries that are straight and those that are tilted on the surface is small, which may result in the disordered orientation of PDI on Au surface. 54 Since the benzene ring and the dipole of methyl group of MPI are in the same plane, the tilt angle of MPI adsorbed on the metal surface should be same as that of the methyl group, which can be quantitatively estimated from the SFG spectra as described below.…”
Section: Resultsmentioning
confidence: 99%
“…Long-chain alkyl thiols are extensively used to form self-assembled monolayers (SAMs) on gold surfaces and their formation and properties have been extensively reviewed. In scanning tunneling microscopy, alkyl thiols on Au(111) initially form so-called “striped phases” in which the alkyl chains lie parallel to the surface to act as precursors to SAM formation. However, rather than the thiolate binding directly to the gold surface, it has recently been found that thiolate species bind to gold adatoms. Such adatom structures are relatively common on coinage metals and have, for example, been implicated in the Ullmann coupling of alkyl halides on copper and gold. Similar adatom-mediated self-assembled structures have also been found using aryl isocyanides on Au(111). The inclusion of two isocyanide groups in trans positions in 1,4-phenylene diisocyanide (PDI) results in the formation of one-dimensional −(Au–PDI) n – oligomers in which each of the isocyanides bind to gold adatoms. The chains propagate via a mobile, vertical Au–PDI adatom complex in which the gold adatom inserts into the terminus of a growing chain …”
Section: Introductionmentioning
confidence: 96%